Comparative Efficacy of Chinese Herbal Injections for Treating Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Bayesian Network Meta-Analysis of Randomized Controlled Trials. (17th July 2018) - Duan, Xiaojiao; Wu, Jiarui; Huang, Xingyue; Wang, Kaihuan; Zhao, Yi; Zhang, Dan; Liu, Xinkui; Zhang, Xiaomeng
Abstract : Introduction . Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) imposes a huge economic burden on healthcare systems worldwide. Chinese herbal injections (CHIs) are widely used to treat AECOPD. In this study, we examined the efficacy of CHIs in the treatment of AECOPD using a network meta-analysis (NMA). Methods . Literature search was conducted from electronic databases of randomized controlled trials (RCTs) on CHIs plus Western medicine (WM) versus WM. WinBUGS 1.4.3 and STATA 12.0 were adopted to compute calculations and prepare graphs, respectively. Results . We included 155 RCTs with 13, 218 patients. The results revealed that Danhong injection (DH) + WM had the greatest therapeutic potential in terms of rate of clinical efficacy (RCE). In addition, in comprehensively improving RCE and FEV1 %, and RCE and C-reactive protein, Huangqi injection (HQ) +WM was associated with preferable effects. Similarly, Xixinnao injection + WM, Reduning injection (RDN) +WM, and HQ+WM had a favorable effect on RCE and PaO2 . The effect of RDN+WM was favorable in all outcomes except RCE. The safety of CHIs needs to be further assessed. Conclusions . Based on this NMA, DH+WM, HQ+WM, and RDN+WM were potential optimal therapies in AECOPD and their safety should be strictly monitored.